Cueing animations: Dynamic signaling aids information extraction and comprehension - Boucheix, J.; Lowe, Richard; Putri, D.; Groff, J. (Pergamon, 2013)
The effectiveness of animations containing two novel forms of animation cueing that target relations between event units rather than individual entities was compared with that of animations containing conventional entity-based cueing or no cues. These relational event unit cues (progressive path and local coordinated cues) were specifically designed to support key learning processes posited by the Animation Processing Model (Lowe & Boucheix, 2008). Four groups of undergraduates (N = 84) studied a user-controllable animation of a piano mechanism and then were assessed for mental model quality (via a written comprehension test) and knowledge of the mechanism's dynamics (via a novel non-verbal manipulation test). Time-locked eye tracking was used to characterize participants' obedience to cues (initial engagement versus ongoing loyalty) across the learning period. For both output measures, participants in the two relational event unit cueing conditions were superior to those in the entity-based and uncued conditions. Time-locked eye tracking analysis of cue obedience revealed that initial cue engagement did not guarantee ongoing cue loyalty. The findings suggest that the Animation Processing Model provides a principled basis for designing more effective animation support.